1993
DOI: 10.1037/0278-7393.19.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Irrelevant tones produce an irrelevant speech effect: Implications for phonological coding in working memory.

Abstract: A series of studies addresses the possibility that tones disrupt serial recall of visually presented material in the same way as speech. A stream of changing tones is as disruptive of visual serial recall as 4 syllables (Experiments 1 and 2). Similar effects were also shown with a repeated syllable that changed only in pitch (Experiment 3). Just as for speech, the effect of tones is not at encoding but during storage of the serial lists (Experiments 4 and 5). The results suggest that speech and tones are equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
590
15
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 378 publications
(643 citation statements)
references
References 24 publications
37
590
15
1
Order By: Relevance
“…1B). Also consistent with previous findings (Jones & Macken, 1993;LeCompte, 1995) the multiple items produced more disruption than the single items did. The literature on irrelevant speech effects between single items and quiet conditions are somewhat mixed.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1B). Also consistent with previous findings (Jones & Macken, 1993;LeCompte, 1995) the multiple items produced more disruption than the single items did. The literature on irrelevant speech effects between single items and quiet conditions are somewhat mixed.…”
Section: Resultssupporting
confidence: 92%
“…There is also a broad agreement with the view that disruption occurs principally when the irrelevant sound fluctuates, termed the 'changing-state hypothesis' by Jones (Jones, 1993;Jones et al, 1992aJones et al, , 1992bJones & Tremblay, 2000). A related phenomenon is the observation that repeating a single item impairs memory much less than do multiple items (Banbury, Macken, Tremblay, & Jones, 2001;Jones & Macken, 1993). The effect principally influences the storage of the order in which items are presented rather than the items themselves (Banbury et al, 2001;Jones, 1993), although some disruption has occasionally been observed when recall of order was not required (LeCompte, 1994(LeCompte, , 1996.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…One example of the interference-by-content approach is the notion that the ISE is a function of the overlap in the phonemes of items in the background sound and the to-be-recalled visual items (Salamé & Baddeley, 1982). Interference-by-content views, however, experience difficulties RUNNING HEAD: DISTRACTION OF ARITHMETIC BY BACKGROUND SPEECH 4 explaining why, for example, non-phonological sounds such as tones, office noise and instrumental music also impair short-term serial recall performance (Jones & Macken, 1993;Perham, Banbury, & Jones, 2007a;Tremblay, Macken, & Jones, 2001). The attentional capture view assumes that sound captures attention away from the focal task, thereby reducing the level of attentional resources available for any demanding focal task (Bell, Röer, Dentale, & Buchner, 2012;Cowan, 1995).…”
Section: Mechanisms Of Auditory Distractionmentioning
confidence: 99%
“…So, the serial processing that dominates serial recall is disrupted by the degree to which the sound embodies cues to order in the form of physical (acoustic) change. Essentially, these cues compete for action: maintaining the order of the to-be-remembered competes for hegemony over the preattentive processing of auditory order cues (Hughes & Jones, 2003a, b, 2005Jones & Macken 1993;. In semantic free recall, this process of competition is countered by inhibition of the irrelevant events (Marsh, Beaman, Hughes & Jones, 2011).…”
mentioning
confidence: 99%